Actinomycosis masquerading recurrent carcinoma after hemicolectomy - A rare case report (Indian Journal of Case Reports, 2024)
Abdominal actinomycosis is a chronic suppurative infection caused by anaerobic bacteria, Actinomyces species. The ileocecal region is most commonly affected, while the left side of the colon is more rarely involved. The presentation may vary from non-specific symptoms and signs to an acute abdomen. We present the case of colonic actinomycosis in a 74-year-old woman who had undergone left hemicolectomy due to carcinoma of the sigmoid colon and became infected with actinomycosis at the anastomotic site, which mimicked local recurrence of cancer. The patient presented with intermittent colicky left-sided abdominal pain for 3 months’ duration. Computed tomography of the abdomen showed a circumferential thickening of the wall of the sigmoid colon surrounded by inflammation. The patient underwent resection of the bowel including the anastomotic site. The macroscopic evaluation revealed mucosal irregularities with abscesses attached to the sigmoid colon and histopathological examination of the specimen revealed actinomycosis of the sigmoid colon with no evidence of malignancy. We are presenting this case to illustrate the preoperative diagnostic difficulties of this rare disease and its ability to mimic malignancy.